Porous alumina based ordered nanocomposite coating for wear resistance. (16th August 2016) - Yadav, Arti; Muthukumar, M; Bobji, M S
Abstract: Uniformly dispersed nanocomposite coating of aligned metallic nanowires in a matrix of amorphous alumina is fabricated by pulsed electrodeposition of copper into the pores of porous anodic alumina. Uniform deposition is obtained by controlling the geometry of the dendritic structure at the bottom of pores through stepwise voltage reduction followed by mild etching. The tribological behaviour of this nanocomposite coating is evaluated using a ball on flat reciprocating tribometer under the dry contact conditions. The nanocomposite coating has higher wear resistance compared to corresponding porous alumina coating. Wear resistant nanocomposite coating has wide applications especially in protecting the internal surfaces of aluminium internal combustion engines.